THE FINANCIAL MARKET OF UKRAINE AND THE ROLE OF FOREIGN DIRECT INVESTMENT - Lyutiy, Igor; Borovikova, Mariya (Ekonomika, 2013)
Abstract. The main objective of this paper is to investigate the characteristics of the institutional structure of the Ukrainian financial market and to analyze the impact of foreign direct investment on it. The following methods of research were used by the authors: economic-statistical, tabular, and comparative (in empirical analysis; to make comparisons across different types of financial institutions, to investigate and evaluate the volumes of foreign direct investment by countries and their relation to the size of the domestic financial sector); systematic and logical (determining and analyzing the scope of the positive and negative effects of foreign investment on the financial market of Ukraine). The conclusions are as the follows: the structure of the financial market of Ukraine is rather nonbalanced and fragile; most foreign investors have changed their strategies on the Ukrainian financial market from aggressive to share-keeping; more attention should be paid to the development of the constructive policy concerning FDI to ensure the stability and even the development of the domestic financial market as well as to raise its investment attractiveness. Key words: financial market, commercial bank, non-bank financial institutions (NBFIs), foreign investment, investment attractiveness